Intergovernmental transfers and public sector expenditures: A game-theoretic approach - Sanguinetti, Pablo (Estudios de Economía, 2016)
It is well known that the fiscal performance of a country is actually determined by the interaction of may fiscal authorities within the public sector. The purpose of this paper is to present a simple model that adopts a game-theoretic point of view to investigate the consequences of different modes of interaction between federal and provincial jurisdictions for the determination of the overall public sector expenditures and taxes. We motivate the theoretical exercises presenting evidence regarding the fiscal performance of Argentina in 1970-1987 where an ill-designed system of intergovernmental grants has been associated with increasing provincial government deficits and of public sector expenditures.